2022
DOI: 10.3389/fcell.2022.983031
|View full text |Cite
|
Sign up to set email alerts
|

The phenotype of the gut region is more stably retained than developmental stage in piglet intestinal organoids

Abstract: Intestinal organoids are innovative in vitro tools to study the digestive epithelium. The objective of this study was to generate jejunum and colon organoids from suckling and weaned piglets in order to determine the extent to which organoids retain a location-specific and a developmental stage-specific phenotype. Organoids were studied at three time points by gene expression profiling for comparison with the transcriptomic patterns observed in crypts in vivo. In addition, the gut microbiota and the metabolome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…Indeed, the expression of LYZ and TLR4 remained reduced in organoids derived from piglets treated with colistin, even after several passages that ensured the elimination of residual microbiota-derived compounds. These results are in line with previous studies showing that tissue-derived intestinal organoids retained some transcriptomic signatures specific to the gut region 38,[64][65][66] and to the disease state. 67,68 In contrast, other studies showed that organoids derived from germ-free or conventional mice did not retain the transcriptomic differences observed in vivo.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, the expression of LYZ and TLR4 remained reduced in organoids derived from piglets treated with colistin, even after several passages that ensured the elimination of residual microbiota-derived compounds. These results are in line with previous studies showing that tissue-derived intestinal organoids retained some transcriptomic signatures specific to the gut region 38,[64][65][66] and to the disease state. 67,68 In contrast, other studies showed that organoids derived from germ-free or conventional mice did not retain the transcriptomic differences observed in vivo.…”
Section: Discussionsupporting
confidence: 92%
“…Previous experiments in the Caco-2 human cell line showed that TMA reduced cell growth but did not alter the epithelial barrier function ( 35 , 36 ). To circumvent the lack of cellular diversity and genomic abnormalities of cell lines, we tested the effects of TMA in suckling piglet colon organoids that contain the main cell types and reproduce the 3D architecture of the intestinal epithelium ( 37 , 38 ). Our results showed that, contrary to our hypothesis, TMA did not alter epithelial homeostasis when considering cell morphology, TEER, and the gene expression of proteins involved in tight-junctions, epithelium renewal, innate immunity, redox enzymes, or ion transport.…”
Section: Discussionmentioning
confidence: 99%
“…We used colon organoids derived from a 21-day-old suckling piglet and cryopreserved at passage 1, as described previously ( 37 ). A cryovial containing colon organoids was thawed at 37°C and centrifuged (at 300 g, 5 min, and room temperature).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes are thought to be largely driven by changes in the luminal environment occurring at weaning, including both gut microbiota composition and nutrients modifications [11]. Mussard et al revealed that porcine organoids derived from pre-(21-day old) and post-weaning (35-day old) piglets harbored very close phenotypes, suggesting that the weaning-induced changes in luminal environment do not imprint piglet ISC [12]. Beside weaning, the neonatal period (from birth to post-natal day 28 in pigs), is also a key period in terms of intestinal development, with changes in epithelium morphology and gene expression with post-natal age [13], as well as ISC dynamics depending on gut location [14].…”
Section: Introductionmentioning
confidence: 99%